2022
DOI: 10.1177/11782218221101011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Substance Use Male Population in East African Countries: A Multilevel Analysis of Recent Demographic and Health Surveys From 2015 to 2019

Abstract: Background: East Africa is still home to one of the world’s highest rates of substance user. Substance use is primarily associated with male behavior and is becoming one of the region’s most public health issues. Methods: The study included data from 11 East African countries’ Demographic and Health Surveys. About 55 307 men were enrolled in the study and multilevel logistic regression model was applied Result: East African countries had a 43.70% prevalence of substance abuse coverage. Education level, age, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…Thus, men with higher educational level were more likely to use alcohol, and alcohol and khat in combination. This result is in line with other studies [ 42 , 51 , 52 ]. This could be explained by educated peoples being largely younger, who are more vulnerable to the use of these substances due to peer pressure, curiosity, and a means to relieve stress [ 53 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, men with higher educational level were more likely to use alcohol, and alcohol and khat in combination. This result is in line with other studies [ 42 , 51 , 52 ]. This could be explained by educated peoples being largely younger, who are more vulnerable to the use of these substances due to peer pressure, curiosity, and a means to relieve stress [ 53 ].…”
Section: Discussionsupporting
confidence: 94%
“…The odds of khat and alcohol use alone or in combination were higher in working men than men who were not working. Studies in East Africa [ 42 ] and Korea [ 47 ] have reported similar findings. The possible reason could be working men are more prone to work-related stress, which might lead to unhealthy coping behavior such as substance use, including khat.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Research on the influence of parental attention on illicit drug use among adolescent boys and young men within the Ugandan context is largely limited. However, although evidence suggests that challenges due to illicit drug use, such as risky sexual behavior and suicidal ideation are greater among males than females [ 24 , 25 ], the present discourse of interventions rarely targets boys. Besides, recent studies have only focused on in-school adolescents [ 26 ], but data for the very young adolescents (10–14 years) are usually missing, since most surveys enroll participants aged 15 years or older.…”
Section: Introductionmentioning
confidence: 99%
“…While socialisation and access to drugs and substances are major drivers of gender variations in drug and substance use in the socio-cultural domain, biological factors such as brain structure and function, endocrine systems, and metabolic processes are important determinants of biological differences in men and women ( McHugh et al, 2019 ). In Sub-Saharan Africa, substance use behaviour is more prominent in males than females ( Fentaw et al, 2022 ). The lifetime and current substance use were 3.2 and 2.8 times higher among males compared to females ( Fentaw et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%